Complications of thoracoscopic TEF clipping for fistula ligation: a case report of polymer clip migration into the right main bronchus and recurrent fistula - Brandau, Annika; Gosemann, Jan-Hendrik; Heublein, Hannes; Thome, Ulrich Herbert; Bläser, Annett; Gräfe, Daniel; Prenzel, Freerk; Lacher, Martin; Wagner, Richard (Frontiers in Pediatrics, 2025)
IntroductionTracheoesophageal fistula (TEF) in neonates with esophageal atresia (EA) is conventionally closed by open or thoracoscopic surgery. We present a case of a rare yet potentially life-threatening complication following thoracoscopic ligation of a TEF, using a polymer clip.Case reportA term boy (GA: 42 + 1 weeks; BW: 3,110 g) underwent thoracoscopic TEF repair for Type C EA. We ligated the fistula using a polymer clip followed by primary esophageal anastomosis on the second day of life. At ten weeks of age, we readmitted the infant due to recurrent bronchitis and episodes of postprandial coughing. Flexible bronchoscopy revealed that the polymer clip, previously employed for fistula closure, had migrated into the right main bronchus and was subsequently retrieved. Despite clip removal, persistent coughing prompted further evaluation, revealing a recurrent TEF on contrast esophagography. An interdisciplinary team successfully obliterated the recurrent fistula using endoscopic chemocauterization with trichloroacetic acid (TCA) via rigid bronchoscopy. Additionally, due to a developing anastomotic stricture, the patient required four balloon dilations and a single triamcinolone injection. At the three-year follow-up, the patient is eating well and thriving normally.ConclusionThis case underscores the potential complications associated with thoracoscopic TEF closure via clipping. The application of transfixing sutures may offer a more secure and durable closure, reducing the risk of post-surgical complications such as clip migration and fistula recurrence.